SO‘Z TURKUMLARINI O‘RGANISh METODIKASI - Atiyazov, S.J. (SCIENCE and SOCIETY, 2025)
This article provides information on the importance of vocabulary learning methodology and how to teach this area. In addition, practical examples and exercises on the methodology of teaching vocabulary using interactive methods will be presented.
Keywords: vocabulary; methodology; interactive methods; language; education; pedagogy